(untitled) (Bangladesh Journal of Medical Science, 2020)
Chronic wounds, particularly infected wounds are clinically very important due to their significant impact on health budgets as well as patients` health worldwide. Patients with diabetes mellitus, vascular diseases especially peripheral vascular disease and pressure ulcers are major categories of patients presenting with chronic wounds. It is known that there are multiple factors determining chronic wound prognosis. The presence of multiple types of pathogenic bacteria, with specific virulence and adherent (biofilm) properties, contribute a significant role to the development of chronic wounds. This review article is based on the research project entitled” An investigation of the impact of bacterial diversity, pathogenic determinants and biofilms on chronic wounds”. The research findings have been published in form of research papers as well as conference posters. The aim of this article is to highlight various important aspects of bacterial impact on wound healing. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.598-602